EFFECTS OF UREA AND ORGANIC FERTILIZER TREATMENTS ON OIL PALM (ELAEIS GUINEENSIS JACQ.) SEEDLING GROWTH IN THE PRE-NURSERY - Sirait, Bilter A.; Bondar, Benito; Simatupang, Uli C.; Manurung, Agnes Imelda (JURNAL DARMA AGUNG, 2025)
The purpose of this study was to determine the effect of urea fertilizer and organic manure derived from goat manure on the growth of oil palm seedlings in the pre-nursery stage. The research was conducted using a factorial Randomized Complete Block Design (RCBD) consisting of two factors. The first factor was urea fertilizer treatment with three levels: U0 = control, U1 = 3 g/polybag, and U2 = 6 g/polybag. The second factor was the dose of goat manure (K) with three levels: K1 = control, K2 = 200 g/polybag, and K3 = 400 g/polybag. The interaction between urea and goat manure doses had a significant effect on plant height, stem diameter, number of leaves, leaf length, leaf width, and leaf area.